Wacana Nasionalisme Kritis dalam Musik Banyuwangian pada Masa Orde Baru - Tallapessy, Albert; Setiawan, Ikwan; Sariono, Agus; Suwargono, Eko (Paradigma: Jurnal Kajian Budaya, 2019)
This article deals with the representation of critical nationalism discourse in Banyuwangian music in the New Order era. By juxtaposing representation and hegemony theory which emphasizes textual-contextual reading, we will analyze the constructions of local metaphors we assume supporting the establishment of nationalism. Such constructions intertwined with the mobilization of the uniqueness of local cultures that contributed to establishing the national culture through which nationalism got its “nutrition”. However, some songwriters constructed critical nationalism by representing unique metaphors related to the characteristics of subaltern subjects that in the midst of their problems songwriters still have, in their silence, critical view toward the ruling faction, without negating their responsibility to guard the nation. The representation of critical nationalism using local metaphors is a critique of the social and economic problems caused by the injustice of development programs as well as a creative strategy to negotiate Using cultures in the midst of modernity.